Worldview Literacy as Educational Praxis: A Response to ‘Religious Literacy’: Some Considerations and Reservations’, Johannes C. Wolfart - Shaw, Martha ca. 20./21. Jh. (Method & theory in the study of religion, 2022)
This response picks up on two key themes identified by Wolfhart: that of the contested aims of “religious literacy” and the lack of an evidence base for its efficacy. Focusing on the context of formal schooling, the idea of “worldview literacy” is presented as an alternative to “religious literacy”. Rather than an outcome of education, “worldview literacy” is presented as a process of encounter in plurality, an educational praxis that brings young people to a greater understanding of the dynamic diversity of worldviews and of themselves as social actors therein. This reconciles what are often seen as competing aims of Religious Education and provides a framework for a more distributed worldviews education. It is suggested that amidst a preoccupation with measurement, attention needs to be refocused on the value of the educational process itself.